2021
DOI: 10.1007/s40145-021-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of multicomponent disilicate (Yb0.2Y0.2Lu0.2Sc0.2Gd0.2)2Si2O7 with molten calcia-magnesia-aluminosilicate

Abstract: Environmental barrier coating (EBC) materials that are resistant against molten calcia-magnesia-aluminosilicate (CMAS) corrosion are urgently required. Herein, multicomponent rare-earth (RE) disilicate ((Yb0.2Y0.2Lu0.2Sc0.2Gd0.2)2Si2O7, (5RE)2Si2O7) was investigated with regard to its CMAS interaction behavior at 1400 °C. Compared with the individual RE disilicates, the (5RE)2Si2O7 material exhibited improved resistance against CMAS attack. The dominant process involved in the interaction of (5RE)2Si2O7 with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…At 1300 C, the reaction speed began to accelerate. The thickness of the reaction layer at different reaction times was consistent with previous studies, indicating the validity of the data [26][27][28][29][30].…”
Section: Water Vapor Corrosion Mechanism Of Y 2 Sio 5 /Si Coatingssupporting
confidence: 90%
See 2 more Smart Citations
“…At 1300 C, the reaction speed began to accelerate. The thickness of the reaction layer at different reaction times was consistent with previous studies, indicating the validity of the data [26][27][28][29][30].…”
Section: Water Vapor Corrosion Mechanism Of Y 2 Sio 5 /Si Coatingssupporting
confidence: 90%
“…It can be summarized from the variation of the elemental proportions shown in Figure 7 that Ca and Si in CMAS continuously permeate into Y 2 SiO 5, leading to the formation of a reaction zone between melted CMAS and Y 2 SiO 5 . This reaction zone can effectively stop the mutual diffusion of elements in CMAS and Y 2 SiO 5 [ 27 , 28 , 29 ]. Therefore, Y is not capable of diffusing into the reaction zone and the CMAS layer, and Mg and Al are only detected in the CMAS layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the decreased thermal conductivity is demanded in order to continuously improve the protective effect of the TBCs and maintain the long-life service of the gas turbine engines safely. Therefore, searching for new materials with low thermal conductivities is one focus in the ceramic field [4][5][6][7][8].…”
Section: Introduction mentioning
confidence: 99%
“…High‐entropy RE silicates, referring to a multiprincipal solid solution consisting of four or more RE components, have attracted wide attention due to its outstanding molten CMAS corrosion resistance and lower thermal conductivity 15,16 . Wang et al 17 . prepared a high‐entropy RE disilicate (5RE 0.2 ) 2 Si 2 O 7 (RE = Yb, Y, Lu, Sc, and Gd) and found that the high‐entropy RE disilicate exhibited a good molten CMAS corrosion resistance, and the thickness of the apatite reaction layer was only 25 μm after corrosion at 1400°C for 20 h. Wang et al 13 .…”
Section: Introductionmentioning
confidence: 99%